Cultural dimensions of nonsuicidal self-injury: A Malaysian perspective - Janet Ann, Fernandez; Rafidah Aga, Mohd Jaladin; Poh Li, Lau (SAGE Publications Inc., 2022)
Self-injury is a perilous and increasingly common behavior that is particularly prevalent among youth. Nonetheless, there is a deep-rooted public stigma towards people who self-injure. Consequently, people who engage in self-injury are reluctant to seek professional help or disclose their experiences to others. This article aims to combat stigma and promote help-seeking behavior by debunking the common myths surrounding self-injury in the Malaysian context. Specifically, this article aims to serve as an eye-opener for Malaysian counselors and other mental health professionals to improve their multicultural knowledge, skills, and attitudes when working with those who self-injure.